Determining Anterior Fontanel Size and Associated Factors Among Term Neonates on the First Day of Life Born at Jimma University Medical Center (JUMC), Southwest Ethiopia: A Linear Regression Model - Sheleme M; Nigatu TA; Gebremariam T; Etefa T; Birhanu A (Dove Medical Press, 2021)
Merga Sheleme,1 Tilahun Alemayehu Nigatu,2 Teka Gebremariam,2 Tesema Etefa,2 Abdi Birhanu1 1School of Medicine, College of Health and Medical Science, Haramaya University, Harar, Ethiopia; 2Department of Biomedical Sciences, College of Medical Sciences, Institute of Health Sciences, Jimma University, Jimma, EthiopiaCorrespondence: Merga ShelemeSchool of Medicine, College of Health and Medical Science, Haramaya University, P.O. Box, 235, Harar, EthiopiaTel +251920963059Email mergasheleme2014@gmail.comBackground: Knowledge of the normal variation in AF size may be helpful to cue early diagnosis of congenital hypothyroidism, hyperthyroidism, cardiac disease, meningitis, degree of dehydration or provide a clue to disorders of neural and skeletal development. However, the data is scarce. Therefore, this study was aimed to determine AF size and associated factors among term neonates on the first day of life born in Jimma University Medical Center (JUMC), Southwest Ethiopia.Methodology: An institution-based cross-sectional study design was used to consecutively sample term and health newborns. Descriptive statistics, one-way ANOVA, independent samples t-test and correlation were implemented. Finally, multiple Linear regressions were used to see the association of the dependent and independent variables at 95% confidence interval. The significance level was declared at < 0.05 p-value.Results: The mean AF size of the study population was 3.018 cm with standard deviation (±SD) of 0.909 cm (range 0.4– 5.50cm). A multiple linear regression analysis revealed that neonatal birth weight (B=0.001, 95% CI: 0.000– 0.001, p=0.000), crown heel length (B=0.048, 95% CI, 0.018– 0.078, p=0.002), labor duration (B= − 0.028, p=0.001, 95% CI: − 0.45; − 0.012), and gender of the neonates (B=− 0.275, 95% CI: − .441; − .109, p=0.001) were statistically significantly associated with AF size. In a multiple linear regression analysis AF size was explained by independent variables by 54.3%.Conclusions: AF size of the study population was 3.018 cm with a standard deviation (±SD) of 0.909 cm. Birth weight, crown heel length, duration of labor, and gender of the neonate were significantly associated with AF size.Keywords: anterior fontanel, associated factors, linear regression, term neonate, Ethiopia